Co-development, co-production and co-dissemination of scientific research: a case study to demonstrate mutual benefits - Woodall, LC; Talma, S; Stefanoudis, P; Et al. (Royal Society, 2021)
Inadequate and inequitable distribution of research capacity and resources limits both the opportunity for leadership and participation in science. It also results in biases of effort, poor and misinterpretation of global patterns and the availability of limited useable knowledge for current challenges. Increased participation in ocean research and decision-making is needed to account for many stressors and challenges. The current intergovernmental attention on the ocean (e.g. UN Decade of Ocean Science for Sustainable Development) and the development of technologies that permit exploration and accelerate exploitation, suggest it is timely to focus on the ocean and its stewardship. Using the principles of co-development, co-production and co-dissemination, this paper uses a case study of a deep reef project in Seychelles to illustrate some activities that can be employed to magnify research outcomes and legacy. We provide examples which ranged from ministerial briefings and planning meetings to joint field work, grant allocation and co-authoring outputs. These activities helped us to align priorities, promote authentic interactions and focus on equitable science. Finally, reflecting on our experiences, we acknowledge the benefits brought by respectful and long-term partnerships, the variety of activities needed to develop these and challenges of maintaining them. In the future we also want to include more opportunities for regional peer-to-peer learning and technology transfer.